Penguatan Literasi Seni Melalui Pembelajaran Tari Tradisional dalam Mewujudkan SDGs 4 (Quality Education) - Maharani, Lissa; Imma Fretisari; Ni Ketut Santi Sukma Melati (Program Studi Pendidikan Tari FBS UNJ, 2025)
This study aims to analyze the empowerment of arts literacy through traditional dance learning in realizing SDGs 4 (Quality Education). The focus of the research is directed at the implementation of Traditional Dance at SMA Negeri 1 Tempunak, West Kalimantan. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation of teachers and students, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusions. The results of the study indicate that traditional dance learning makes a significant contribution to improving the quality of 21st-century education. Teachers have integrated local cultural values ​​into teaching and learning activities despite being limited by learning resources and understanding of arts literacy. Students showed improvements in critical thinking skills, creativity, communication, collaboration, and understanding of cultural meaning. Traditional dance learning has proven to be an effective arts literacy medium in developing students' cognitive, affective, and psychomotor potential while fostering character and love for national culture. Thus, the conclusion is that the implementation of traditional dance-based arts learning not only strengthens arts and cultural literacy but also supports the achievement of Sustainable Development Goal (SDG) 4 through inclusive, contextual, and sustainable education.